Development of Bamboozle Interactive Learning Media on Office Technology Equipment and Application Elements - Sofiyanti, Nadia; Puspasari, Durinda (Perspektif Ilmu Pendidikan, 2025)
This study aims to develop Bamboozle-based interactive learning media for the subject of Information Technology, specifically Office Technology Equipment and Applications, in class X MPLB 3 at SMKN 10 Surabaya. The background of this study is based on the low utilization of learning media, which is still limited due to the dominant use of whiteboards with markers, as well as the fact that student learning outcomes have not yet reached the minimum competency standard (KKM). The method used was research and development (R&D) with a modified ADDIE model, which included the stages of analyze, design, development, and implementation. The resulting media product was an interactive quiz with features such as material, instructions for use, and practice questions based on the Bamboozle application. The results of validation by subject matter experts obtained a percentage of 96% to 98% in the “very feasible” category. Limited trials were conducted on 20 students in terms of response, reaction, and confidence, with a percentage score above 98% with the criteria “very feasible”. Students rated this media as visually appealing, relevant to learning needs, and capable of increasing motivation and learning engagement. Thus, the Bamboozle interactive learning media is suitable for use as a learning support tool to improve material comprehension, learning enthusiasm, and create a more active and enjoyable classroom atmosphere.